Multichannel Communications in Wireless Automation: Interdependencies between Communication and Control Parameters. (29th March 2012) - Nieminen, Jari; Björkbom, Mikael; Jäntti, Riku; Eriksson, Lasse
Abstract : Exploitation of wireless communications in various automation applications brings indisputable benefits, which has proliferated research efforts in the field during the recent years. However, underlying wireless communication systems introduce problems to the wireless control systems, such as variable delays, information loss, and limited throughput. By using multiple frequency bands simultaneously, the performance of a wireless network can be enhanced. Since many control applications have strict requirements on delay and delay variations, it is important to understand the impact of communication systems on the performance of wireless automation systems with respect to delay. Hence, in this paper, we study how different communication parameters, such as packet arrival rate, number of channels, and packet size, affect the performance of control systems. We also derive bound on control system performance given the network properties. Our results show the tradeoff between the performance of the wireless multichannel communication system and the automation system. These results can, for example, be further exploited in system design to find out the maximum packet arrival rate with given control parameters.